2015
DOI: 10.1038/nsmb.3018
|View full text |Cite
|
Sign up to set email alerts
|

Cryptochrome 1 regulates the circadian clock through dynamic interactions with the BMAL1 C terminus

Abstract: The molecular circadian clock in mammals is generated from transcriptional activation by the bHLH-PAS transcription factor CLOCK–BMAL1 and subsequent repression by PERIOD and CRYPTOCHROME (CRY). The mechanism by which CRYs repress CLOCK–BMAL1 to close the negative feedback loop and generate 24-hour timing is not known. Here we show that CRY1 competes for binding with coactivators to the intrinsically unstructured C-terminal transactivation domain (TAD) of BMAL1 to establish a functional switch between activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
240
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(259 citation statements)
references
References 66 publications
19
240
0
Order By: Relevance
“…Thus, earlier appearance of the Cry1 in the pituitaries of hGH1 TG mice on the HFD may lead to repression of the Bmal1-Clock protein complex, which in turn signals an increase in Bmal1 production and increased RNA levels. A positive trend in Clock expression during the dark cycle by HFD was also observed, although it did not reach statistical significance (55).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Thus, earlier appearance of the Cry1 in the pituitaries of hGH1 TG mice on the HFD may lead to repression of the Bmal1-Clock protein complex, which in turn signals an increase in Bmal1 production and increased RNA levels. A positive trend in Clock expression during the dark cycle by HFD was also observed, although it did not reach statistical significance (55).…”
Section: Discussionmentioning
confidence: 88%
“…These increases in Bmal1 and Cry1 transcript levels with a HFD have been reported previously (54) and may reflect a disrupted feedback system. Evidence suggests that a physical interaction between Cry1 and Bmal1 is responsible for switching Bmal1 from an activated to a repressive state (55). Thus, earlier appearance of the Cry1 in the pituitaries of hGH1 TG mice on the HFD may lead to repression of the Bmal1-Clock protein complex, which in turn signals an increase in Bmal1 production and increased RNA levels.…”
Section: Discussionmentioning
confidence: 99%
“…Based on ChIP-Seq studies, these complexes appear to remodel or reform over time, evolving to a late repressive complex where CRY1 is bound to CLOCK:BMAL1 on DNA, apparently independently of PER (7).These findings suggest that cryptochromes can work both together and separately from PER to repress CLOCK:BMAL1 activity (8)(9)(10). We showed that tuning affinity of CRY1 for the transactivation domain (TAD) of BMAL1 controls circadian period by competing with the coactivator CBP/p300 (11). CRY1 also binds to CLOCK, although it is not yet understood how multivalent interactions with CLOCK: BMAL1 contribute to CRY1 function.…”
mentioning
confidence: 97%
“…The repressive activity of CRY1 is essential to generate circadian rhythms (13)(14)(15); one way that CRY1 does this is by binding the BMAL1 TAD to sequester it from coactivators (11,16). However, CRY1 has only moderate affinity (K d ∼1 μM) for the isolated TAD (11,17), suggesting that it makes at least one other interaction with CLOCK:BMAL1 that allows it to serve as a potent repressor when expressed to near stoichiometric levels (18). Previous studies suggest the CLOCK PAS-B domain is important for repression by CRY1 (11,19,20), but evidence for a direct interaction is lacking.…”
Section: Cry1mentioning
confidence: 99%
“…1d) appears to be responsible for transcriptional repression in Drosophila and mammals [77][78][79][80][81][82][83]. Specifically, in these organisms, repressors sequester activators in a 1:1 stoichiometric complex, which inhibits the transcriptional activity of activators.…”
Section: Introductionmentioning
confidence: 99%